The influence of organizational culture on knowledge management BCS Polska as a case study - Apanasik Barbara (My University, 2008)
The purpose of this thesis is to find out what is the influence of organizational culture on knowledge management, with a main highlight on the process of knowledge sharing. The study was conducted in a highly technologically advanced company, BCS Polska, using the Harrison-Stokes approach for evaluating the organizational culture and original questionnaires for the assessment of knowledge management practices. The company’s organizational culture was found to be achievement-oriented with some positive features of Role and Support cultures and that it has a very positive influence on the company’s knowledge management process. The company intangible and tangible resources are handled in an innovative way, typical for an achievement culture. The atmosphere in the organization creates a fertile ground for knowledge cultivation. Nevertheless, there were still some problems discovered in the field of knowledge sharing and information availability. However, since BCS Polska has all the features of a learning organization, it is very likely to easily overcome them.
Wpływ kultury organizacyjnej na zarządzanie wiedzą na przykładzie BCS Polska
Keywords: organizational culture; knowledge management; Harrison-Stokes approach; learning organization; management